Management of Educator Recruitment at SMPIT Insan Kamil Batusangkar - Fadriati Fadriati (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
This study aims to determine the planning, organization and supervision of the recruitment of educators at the Integrated Islamic High School (SMPIT) managed by the Sepakat Maju Batusangkar Foundation, West Sumatra. This research was conducted at SMPIT Batusangkar. The research method used is a phenomenological research method with a qualitative data processing approach. The main sources of data for the study were the Chairman of the Foundation Trustees, the Chairman of the Foundation and the Principal of SMPIT Insan School Kamil Batusangkar using interviews, observations and documentation studies. The data analysis technique used is the three-step Miles and Huberman model, namely data reduction, data presentation and drawing conclusions. The data validity testing technique uses a credibility test. The findings show that the management of educator recruitment at SMPIT Insan Kamil Batusangkar begins with planning that includes needs analysis, preparation for recruitment, and determination of recruitment qualifications. The organization of the recruitment of educators is also going well, in particular by collaborating and coordinating with the various stakeholders, ranging from the foundation to the committee of the recruitment team. Recruitment of educators is done through the posting of recruitment announcements via social media, websites, and printed brochures regarding acceptance of registration, selection of educators, and decisions on educator recruitment. Supervision is also done properly from the foundation and the school principal to the implementation committee and the implementation process.